PEMBERDAYAAN KELOMPOK PKK DALAM PENGELOLAAN SAMPAH RUMAH TANGGA BERBASIS 3R TERINTEGRASI BANK SAMPAH DI DESA CIBODAS, KECAMATAN PASIRJAMBU, KABUPATEN BANDUNG - Dwi Indrawati; Pramiati Purwaningrum; Ratningsih Ruhiyat; Etty Indrawati (JUARA: Jurnal Wahana Abdimas Sejahtera, 2022)
Community empowerment, which is the practice of implementing 3R by utilizing or recycling household solid waste, aims to increase the community's knowledge and skills in utilizing household solid waste into economic value products. Having this knowledge and skills will increase people's interest and willingness to use household solid waste, which in turn will maintain environmental quality by reducing the amount of solid waste and making the environment greener. This community service activity in Cibodas Village, Pasirjambu District starts from the preparation, implementation, monitoring, and evaluation stages, as well as preparing reports and activity outputs. Activities are carried out offline while still observing health protocols, which are mandatory to wear masks, maintain distance, and always wash hands with soap and running water or use hand sanitizers. In this activity, the implementation is carried out by utilizing material delivery technology through the MS Power point application, delivery interactions through banners/posters, demonstrations of waste sorting and processing practices, as well as the design of 3R-based household waste management patterns that are integrated with the Waste Bank. In the implementation of counseling and training held at the Cibodas Village Office, all participants seemed enthusiastic in gaining additional knowledge and skills in 3R-based household solid waste management and had the motivation to change behavior in placing solid waste in segregated containers.